Charity Rankings: Delivering Development or Dehumanising Aid?. (1st December 2015) - Cochrane, Logan; Thornton, Alec
Abstract: Individuals want to know which organisations to donate to, and a variety of organisations have developed ranking systems to guide them. This paper explores charity ranking, with a particular focus on the increasing role of impact and 'cost‐effectiveness'. Ranking systems are composed of a selection of metrics, which may miss important components and, as a result, create a set of unintended outcomes. We argue that an emphasis on cost‐effectiveness and impact in ranking promotes simple, technocratic activities, negatively affects human rights‐based interventions and de‐prioritises inventions that work in remote, complex settings. The topic of charity ranking and its influence on private donors is limited in the literature, and this paper seeks to make a contribution to this important debate. Copyright © 2015 John Wiley & Sons, Ltd.